Dreams under glass : a novel - Szilágyi, Anca L. (Lanternfish Press, 2022)
"As the economy collapses around her in 2008 New York City, recent art school graduate Binnie takes a job as a paralegal to pay the bills. As her art projects languish on the back burner, she begins to obsessively imagine her daily grind expressed in unsettling and sometimes violent dioramas. Somehow, someday, she'll find the time to construct them. In the meantime, she'll walk this unsatisfying tightrope between financial stability and the life of a working artist. But after a shocking and surreal death occurs at the law firm, Binnie wonders if her frustration is pushing her darkest imaginings into life"--Back cover